Double Taxation Conventions, Structure and Evolution of the American Tax System - DUMITER, Florin; BERLINGHER, Daniel; OPREÈš, Anca; TODOR, Silvia (Journal of Legal Studies, 2016)
This article is intended as a retrospective survey of the comprehensiveness of the tax system, in the broad sense, and the US tax system, in a stricter sense, in terms of structuring model and application of tax levies, as well as the taxation applied to each public financial income category. The topic chosen is based on the idea that the US tax system is different from the European system, while also considering that the USA is the world leader in business, trade and investment, and seen as a true "streamliner" of the world. The US economy is strongly influenced by sectors that prevail at the federal level: industry, education, trade, telecommunications, and transportation. The research methodology used in this article consists of a comprehensive analysis of key concepts regarding tax levying activities, providing an explanation of the tax policy, a critical analysis of the US system in terms of tax legislation, and a history of international double taxation conventions concluded by the US with other countries, given that the USA may be an archetype (best practice) in terms of the double taxation agreements network, regarding both the number of countries with which they have been concluded, and the types of agreements on income and capital. In our opinion, the results of this study indicate the optimal technical framework used by the American system to identify and implement the most sustainable methods, techniques and procedures in order to reduce the scope of international double taxation on income and capital worldwide.